Early detection of recurrent laryngeal nerve damage using intraoperative nerve monitoring during thyroidectomy. Issue 1 (January 2020) - Yu, Tian; Wang, Fei-liang; Meng, Ling-bing; Li, Jian-kun; Miao, Gang
Objective: This study aimed to investigate risk factors for early recurrent laryngeal nerve (RLN) damage during thyroid surgery with intraoperative nerve monitoring (IONM) technology to avoid RLN damage during surgery. Methods: Data were retrospectively collected from 93 patients who underwent thyroidectomy at Beijing Hospital. All operations were performed by the same surgeon. A four-step procedure of IONM was used during the operation to determine the amplitude and latency of the RLN. Results: The majority (51.6%) of patients who underwent surgery had thyroid carcinoma. Lymphadenectomy was carried out in 55 (59.1%) patients. A strong association was observed between temporary injury of the RLN and the extent of resection. The risk of temporary injury of the RLN during total thyroidectomy was three times that during right thyroid lobectomy (odds ratio = 3.13). The results of left lobectomy were also different from those of right lobectomy because the RLN was more likely to be damaged during left lobectomy. Conclusions: Assessment of the amplitude and latency of the RLN can help to assess the integrity of the RLN. The extent of resection affects the functional integrity of the RLN.